2017
DOI: 10.1002/2016gl070923
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability in ozone removal by a temperate deciduous forest

Abstract: The ozone (O3) dry depositional sink and its contribution to observed variability in tropospheric O3 are both poorly understood. Distinguishing O3 uptake through plant stomata versus other pathways is relevant for quantifying the O3 influence on carbon and water cycles. We use a decade of O3, carbon, and energy eddy covariance (EC) fluxes at Harvard Forest to investigate interannual variability (IAV) in O3 deposition velocities ( vd,O3). In each month, monthly mean vd,O3 for the highest year is twice that for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 119 publications
7
87
1
Order By: Relevance
“…For the most part, we use the L15 and W15 g s estimates to support our findings with P‐M g s . Clifton et al () find similar interannual variability in g s estimates from L15 and P‐M, so we are fairly confident that P‐M represents g s variations on this timescale. We are less confident in the ability of P‐M g s to represent subseasonal variability in g s due to changes in evaporation with rain and aridity.…”
Section: Methodssupporting
confidence: 79%
“…For the most part, we use the L15 and W15 g s estimates to support our findings with P‐M g s . Clifton et al () find similar interannual variability in g s estimates from L15 and P‐M, so we are fairly confident that P‐M represents g s variations on this timescale. We are less confident in the ability of P‐M g s to represent subseasonal variability in g s due to changes in evaporation with rain and aridity.…”
Section: Methodssupporting
confidence: 79%
“…Non-stomatal dry deposition is increasingly been recognized to be crucial for removal of O 3 from the atmosphere (Altimir et al, 2006;Fares et al, 2010;Clifton et al, 2017). There exist, however, multiple pathways of non-stomatal deposition Fowler et al, 2009) and this knowledge is required for inclusion in current model parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…This partly reflects the range of different processes involved, from adsorption and chemical take-up in plant stomata (Fowler et al, 2009) to iodine-mediated removal at the ocean surface (PradosRoman et al, 2015). Analysis of observational studies of the processes controlling ozone deposition shows that the importance of different deposition pathways differs by location as well as by season and from year to year at each location (Rannik et al, 2012;Clifton et al, 2017). Comparison of dry deposition fluxes from 15 global models involved in the TF HTAP model intercomparison project (Table 1) found that differences in ozone dry deposition are strongly influenced by differences in land cover classification used in models (Hardacre et al, 2015).…”
Section: Wet and Dry Depositionmentioning
confidence: 99%